Patients with endometriosis may experience worse clinical manifestations and therapeutic outcomes during COVID-19 in western China- a case series comparative analysis - Sanhong Liu; Cong Hou; Sisi Tang; Shutong Bai; Ying Deng (BMC, 2023)
Abstract Background Endometriosis is a crippling, ongoing, chronic inflammatory condition. The management of these patients has been impacted by the current COVID-19 pandemic, which is still controversial. This study compared the clinical therapy outcomes and psychological scores between before and during- the epidemic. Method The data of patients who were diagnosed with endometriosis in the Department of Gynecology, Chongqing Traditional Chinese Medicine Hospital from January 2018 to December 2022 were collected. The patients were divided into pre- and intra-COVID groups. The treatment results and psychological status of the two groups were compared. Results A total of 1022 patients with endometriosis were enrolled, with a mean age of 33.16 ± 9.81 years and a BMI of 23.90 ± 3.04 kg/m2, of which 434 cases (434/1022, 42.5%) were in the pre-COVID group and 588 cases (588/1022, 57.5%) in the intra-COVID group. Both groups were well balanced for age, BMI, history of abdominopelvic surgery, family relationships, education level, and duration between initial diagnosis and admission. Compared to the Pre-COVID group, the intra-COVID group had a higher proportion of patients with chronic pelvic pain (297/434, 68.4% vs. 447/588, 76.0%, p = 0.007) and dysmenorrhea (249/434, 62.8% vs. 402/588, 70.0%, p < 0.001), more patients requiring surgery (93/434, 21.4% vs. 178/588, 30.3%, p = 0.002) and longer hospital stays (5.82 ± 2.24 days vs. 7.71 ± 2.15 days, p < 0.001). A total of 830 questionnaires were completed. In the Intra-COVID group, PHQ-2 (2 (2, 3) vs. 3 (2,4), p < 0.001), GAD-2 (2 (1, 2) vs. 3 (2, 3), p < 0.001), PHQ-4 (4 (3, 5) vs. 5 (4, 7), EHP-5 (20.26 ± 6.05 vs. 28.08 ± 7.95, p < 0.001) scores were higher than that in the pre-COVID group, while BRS (3.0 (2.2, 4.0) vs. 2.4 (1.8, 3.8), p = 0.470) were not significantly different. Conclusion During the COVID-19 epidemic, patients with endometriosis may have reduced visits to the hospital, more severe related symptoms, longer length of hospital stays, and worse quality of life, with the possible cause being a disturbance in hormone levels through increased anxiety and depression. This provides a valid clinical basis for optimizing the management of patients with endometriosis and for early psychological intervention during the epidemic.